2015
DOI: 10.1590/2359-3997000000042
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Charcot foot

Abstract: Objective: Diabetes mellitus is the main cause of Charcot neuroarthropathy and is clinically classified as follows: Charcot foot, acute Charcot foot (ACF) when there is inflammation, and inactive Charcot foot when inflammatory signs are absent. The aim of this study was to identify the risk factors for ACF in patients with type 2 diabetes mellitus. Materials and methods: A matched case-control study was conducted to assess the factors associated with acute Charcot foot from February 2000 until September 2012. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Additionally, the increased blood flow may directly cause increased bone resorption by increasing the delivery of osteoclasts and monocytes resulting in greater osteoclastic activity in this area [ 15 ]. This is consistent with the finding that patients with a Charcot foot show increased blood flow to the area whereas patients with peripheral arterial disease and diabetes are relatively protected from developing the arthropathy [ 16 , 17 ].…”
Section: Pathogenesissupporting
confidence: 89%
See 3 more Smart Citations
“…Additionally, the increased blood flow may directly cause increased bone resorption by increasing the delivery of osteoclasts and monocytes resulting in greater osteoclastic activity in this area [ 15 ]. This is consistent with the finding that patients with a Charcot foot show increased blood flow to the area whereas patients with peripheral arterial disease and diabetes are relatively protected from developing the arthropathy [ 16 , 17 ].…”
Section: Pathogenesissupporting
confidence: 89%
“…Other studies report the most patients with DNOAP in their sixth and seventh decades [ 2 , 52 ]. Fauzi et al [ 16 ] and Nobrega et al [ 17 ] reported that age below 60 and 55 years were significant risk factors for DNOAP respectively.…”
Section: Relative Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Charcot foot (CF) disease is a rare (0.08–7.5%) but extremely debilitating complication in patients with diabetes 1 , which can result in amputation and increased mortality 2 . Indeed the life expectancy of patients with CF is reduced by ~14.4 years 3 .…”
Section: Introductionmentioning
confidence: 99%